Enhancing undergraduate critical listening through Discord-based video chain-question strategy - ramadhan, Iqbal; Mubarok, Harir; R, Kenny Shania Lestari (Proceeding of International Conference on Islamic Education (ICIED), 2025)
The advancement of digital technology has reshaped language learning, demanding pedagogical approaches that foster higher-order skills. Critical listening, the ability to evaluate and analyze spoken content, is crucial in higher education, yet students often struggle to develop it in online settings that lack interaction. This study addresses this gap by investigating the effectiveness of the Video Chain-Question strategy, implemented via the Discord platform, in enhancing the critical listening skills of undergraduate EFL students. This study employed a developmental research (R&D) design following the 3PS Model (Analysis, Strategy, Application & Evaluation). Twenty fifth-semester students from an International Class Program participated in the research. The intervention used authentic documentary videos within Discord's collaborative environment. Data were collected using pre-tests and post-tests, and subsequently analyzed using a Paired Sample T-Test. The findings revealed a statistically significant improvement in students' critical listening abilities following the intervention. The results of this study indicate that there is a significant difference between the pre-test and post-test, with 92% of scores being above average. The needs analysis also confirmed that both students and lecturers were active technology users, validating the choice of Discord as an alternative LMS. The results suggest that the integration of the Video Chain-Question strategy within Discord creates a dynamic, interactive, and effective environment that successfully enhances students' critical listening skills.